Regulation of Expression of Oxacillin-Inducible Methionine Sulfoxide Reductases in Staphylococcus aureus - Kyle R. Baum; Zulfiqar Ahmad; Vineet K. Singh (International Journal of Microbiology)
Cell wall-active antibiotics cause induction of a locus that leads to elevated synthesis of two methionine sulfoxide reductases (MsrA1 and MsrB) in Staphylococcus aureus. To understand the regulation of this locus, reporter strains were constructed by integrating a DNA fragment consisting of the msrA1/msrB promoter in front of a promoterless lacZ gene in the chromosome of wild-type and MsrA1-, MsrB-, MsrA1/MsrB-, and SigB-deficient methicillin-sensitive S. aureus strain SH1000 and methicillin-resistant S. aureus strain COL. These reporter strains were cultured in TSB and the cellular levels of β-galactosidase activity in these cultures were assayed during different growth phases. β-galactosidase activity assays demonstrated that the lack of MsrA1, MsrB, and SigB upregulated the msrA1/msrB promoter in S. aureus strain SH1000. In S. aureus strain COL, the highest level of β-galactosidase activity was observed under the conditions when both MsrA1 and MsrB proteins were absent. The data suggest that the msrA1/msrB locus, in part, is negatively regulated by MsrA1, MsrB, and SigB in S. aureus.